Embodying virtue in employment: Exploring the employment experiences of people with disabilities - Bam, Armand (Research of GSB, 2018)
Research on the employment experiences of people with disabilities (PWD), on a global level, is limited. While South Africa has a well-defined legislative framework that has been determined in consultation with disabled people's organisations, compliance with legislation appears to have failed to ensure that employment targets are met, or rather, it has overlooked the underemployment of PWD. As a response to the challenges, this study explored the employment experiences of PWD. A qualitative, explorative, multiple case study approach was employed. Twelve participants were selected using a purposive technique. Semi-structured interviews were used to collect data and provided insight into how PWD viewed their world. The interviews were supplemented through document analyses, and various modes of observation provided additional insight into each of the cases. The process of analysing the interview data followed an inductive approach during which three broad themes were identified. Factors influencing Employment elaborated on the participants' pre-employment experiences of gaining access to employment, which were shown to be impacted by various environmental barriers. Early Experiences of Inclusion at the Workplace established that induction and orientation processes were opportunities for educating co-workers about disability. However, the disclosure of disability did not guarantee improved employment experiences for the research participants. Feeling part of a team promoted early experiences of acceptance. Accommodation in the Workplace determined that PWD's accommodation requests were often evaluated and considered in terms of the costs to employers, and primarily focused on technology to improve their productivity. The need for personal assistance for the PWD in the study was found to be unavoidable. A conceptual model is presented as an alternative framework. It offers insight into how to improve disabled individuals' employment experiences to organisations and their management, and people with disabilities themselves. The model suggests that organisations operating from within a virtue framework can facilitate equal opportunities for employees. Organisations are to be more competitive, innovative and creative, and improve their sustainability. The experiences of PWD could be improved through establishing working communities within organisations as these distribute decisionmaking. The climate for organisational inclusion could also be improved by the working community's ability to redefine work and equip PWD appropriately, thereby promoting organisational citizenship, with benefits to both the organisation and individual.